THE USE OF CASSAVA LEAVES AS A DIETARY COMPONENT FOR AFRICAN CATFISH FRY - Amalia Sutriana (Universitas Syiah Kuala, 2007)
An experiment was carried out to evaluate the effect of graded levels of cassava leaf meal (CLM) with varying cyanide content on growth performance of African catfish (Clariasgariepinus) fry. There were four groups of fish, each comprising 12 fish per group. One groupwas fed on a control diet (0 mg HCN/kg diet) with fish meal (FM) and soybean meal (SBM) asprotein source (30% CP). Groups two, three and four were fed graded levels of CLM to replace10, 20, and 30% of the total diet at the expense of SBM which contains 4.19, 7.47 and 11.96 mgHCN/ kg diet respectively. After 12 weeks, fish fed with increasing level of CLM showed asignificant growth depression and poor feed utilization compared to those fed the control diet.Apparent dry matter digestibility (ADMD) and apparent protein digestibility (APD) were alsosignificantly (P0.05) affected by cassava leaf meal inclusion, with the best values were found infish fed the control diet (52.26+0.24% and 83.11+1.17% for ADMD and APD respectively). Bodycomposition of fish fed higher CLM tended to have less protein and fat but more ash. The poormethionine availability as a result of low protein digestibility and the presence cyanide contentlimits the use of CLM in African catfish fry diet.Keywords: African catfish, cassava, growth, cyanide